(untitled) (Research, Society and Development, 2021)
In view of the devaluation of Brazilian education and science observed in recent years and considering the importance of Physiology as basic science it is necessary to carry out the general mapping of this area by analyzing the profile of productivity researchers fellows and, therefore, highlight possible discrepancies existing between the different levels of categories. This is an observational, descriptive study. Free access was made to the information contained on National Council for Scientific and Technological Development website for the identification of PQ fellows. We found 193 PQ fellowship in Physiology, 72% of which were located in the Southeast region. We also observed a predominance of male fellowships (54.9%). Regarding the distribution by public and private sectors, 94.8% were in the public service. Among the Institutions where the researchers were located, 6 of them are responsible for 52.4% of the PQ fellowships. When analyzing the total number of PG programs reposted in the Lattes, we found a total of 152 PG programs, of which 46 are in the area of CBII. We conclude that although researchers from all over the Brazilian territory may apply for a Productivity Grant, these are still concentrated in the Southeast region, thus revealing the disparity in distribution. We also highlight the distribution of fellowship by sex, indicating a predominance of males, especially at higher hierarchical levels. Based on our data, the most researchers are linked to only one graduate program and 27.6% of them are allocated to the area of Biological Science II.